ESG ratings rewriting or recalibration? - ZHANG, Chengshuang (Institutional Knowledge at Singapore Management University, 2023)
ESG ratings are the nexus of sustainable development. Are ongoing retroactive adjustments of ESG scores rewriting or recalibration? Using datasets from 20 random weeks of downloads of Refinitiv ESG universe between 7 October 2021 to 14 December 2022, we find that the positive link between ESG scores or E&S scores to firms’ stock returns existed between 2011 to 2017, disappeared between 2002 to 2011 and attenuated between 2017 to 2021. Using the formation of the International Sustainability Standard Board on 3rd November 2021 as the external shock event, we further find that the retroactive ESG score adjustments are not driven by stock returns and therefore are likely recalibrations. We extend (Berg et al., 2020a)’s findings that ongoing retroactive ESG score adjustments are rewritings driven by firms’ stock returns, a classic agency problem. We could not validate such findings with scientific evidence on our randomly downloaded datasets closer to the date. The positive link is time frame dependent; while ongoing retroactive ESG score adjustments are prevalent, it postulates recalibration.